Optimasi Perbandingan Pelarut dan Lama Maserasi terhadap Kadar Total Antosianin Ekstrak Jantung Pisang (Musa acuminata x Musa balbisiana) - Yunita Widyastutik; Prisma Trida Hardani; Dewi Perwito Sari (Universitas Muhammadiyah Surakarta, 2022)
The inflorescence of the banana plant has not been widely used as a natural remedy. The inflorescence is known to contain anthocyanin compounds that have a variety of benefits. This study aimed to determine the anthocyanin content. This study used the ratio of materials: solvents of 1:5 and 1:9 as well as extraction time of 6 hours and 24 hours. Total anthocyanin levels were determined by the pH-differential method using pH 1.0 and pH 4.5 buffers. The best extraction conditions are determined by measuring the total anthocyanin levels. The data obtained were statistically analyzed by two-way variance analysis (Two Way ANOVA). The results showed that the ratio of the material to the solvent with the highest anthocyanin content was 1:9 with an extraction time of 6 hours. The extraction resulted in a yield of 2.64% and a total anthocyanin content of 0,119 g / 100 grams. This shows that the extraction duration affects the total level of anthocyanins and is statistically meaningful (p = 0.0010.05).